Region-specific gene expression profiling of early mouse mandible uncovered SATB2 as a key molecule for teeth patterning - Nevoránková, Petra; Šulcová, Marie; Kavková, Michaela; Zimčík, David; Balková, Simona Moravcová; Peléšková, Kristýna; Kristeková, Daniela; Jakešová, Veronika; Zikmund, Tomáš; Kaiser, Jozef; Holá, Lydie Izakovičová; Kolář, Michal; et al. (Scientific reports, 2024)
Mammalian dentition exhibits distinct heterodonty, with more simple teeth located in the anterior area of the jaw and more complex teeth situated posteriorly. While some region-specific differences in signalling have been described previously, here we performed a comprehensive analysis of gene expression at the early stages of odontogenesis to obtain complete knowledge of the signalling pathways involved in early jaw patterning. Gene expression was analysed separately on anterior and posterior areas of the lower jaw at two early stages (E11.5 and E12.5) of odontogenesis. Gene expression profiling revealed distinct region-specific expression patterns in mouse mandibles, including several known BMP and FGF signalling members and we also identified several new molecules exhibiting significant differences in expression along the anterior-posterior axis, which potentially can play the role during incisor and molar specification. Next, we followed one of the anterior molecules, SATB2, which was expressed not only in the anterior mesenchyme where incisor germs are initiated, however, we uncovered a distinct SATB2-positive region in the mesenchyme closely surrounding molars. Satb2-deficient animals demonstrated defective incisor development confirming a crucial role of SATB2 in formation of anterior teeth. On the other hand, ectopic tooth germs were observed in the molar area indicating differential effect of Satb2-deficiency in individual jaw regions. In conclusion, our data provide a rich source of fundamental information, which can be used to determine molecular regulation driving early embryonic jaw patterning and serve for a deeper understanding of molecular signalling directed towards incisor and molar development.
Keywords: Tooth; vazebné proteiny DNA v oblastech připojení k matrix; Lower jaw; rozvržení tělního plánu; vývojová regulace genové exprese; Incisor; Odontogenesis; Molar; Gene Expression Regulation, Developmental; signální transdukce; Mouse; stanovení celkové genové exprese; Signal Transduction; Gene Expression Profiling; řezáky; Microarray; Mandible; Animals; Transcription Factors; transkripční faktory; mandibula; odontogeneze; zvířata; Body Patterning; myši; Satb2; Matrix Attachment Region Binding Proteins; Mice; zuby